Developmental regulation of GABAergic gene expression in forebrain cholinergic neurons - Granger, Adam J.; Mao, Karen; Saulnier, Jessica L.; Hines, Morgan E.; Sabatini, Bernardo L. (Frontiers in Neural Circuits, 2023)
Acetylcholine and GABA are often co-released, including from VIP-expressing neurons of the cortex, cortically-projecting neurons of the globus pallidus externus and basal forebrain, and hippocampal-projecting neurons of the medial septum. The co-release of the functionally antagonistic neurotransmitters GABA and acetylcholine (ACh) greatly expands the possible functional effects of cholinergic neurons and provides an additional exogenous source of inhibition to the cortex. Transgene expression suggests that nearly all forebrain cholinergic neurons in mice at some point in development express Slc32a1, which encodes the vesicular GABA transporter (VGAT). To determine the degree of co-expression of GABA and Ach handling proteins, we measured expression in adult mice of Slc32a1, Gad1 and Gad2 (which encode GAD67 and GAD65, respectively, the GABA synthetic enzymes) in cholinergic neurons using fluorescent in situ hybridization. We found that only a subset of cholinergic neurons express the necessary machinery for GABA release at a single time in adult mice. This suggests that GABA co-release from cholinergic neurons is dynamic and potentially developmentally regulated. By measuring expression of Slc32a1, Gad1, Gad2, and Chat in the basal forebrain and medial septum in mice from post-natal day 0 to 28, we noted abundant yet variable expressions of GABAergic markers across early development, which are subsequently downregulated in adulthood. This is in contrast with the forebrain-projecting pedunculopontine nucleus, which showed no evidence of co-expression of GABAergic genes. These results suggest that expression of GABA signalling machinery in cortically-projecting cholinergic system peaks during early development before settling at a non-zero level that is maintained through adulthood.